Shiqaq dan Penyelesaiannya dalam Hukum Islam - Trigiyatno, Ali (Al-Manahij: Jurnal Kajian Hukum Islam, 2010)
Marriage which is intended to buid a good and blased family sometimes gets a trouble such as disloyality. Disloyality might be done by husband, wife or both of them. Shiqaq therapy is usually applied to overcome disloyality by having two people (hakam) from both side to find the best solution such as reconciliation or a recommendation to get divorce.